Analysis of Human Resources Development Strategy in Increasing Employee Productivity at PMKS PT. Pandawa's Ray - Sahputri, Andriani; Aslami, Nuri; Dharma, Budi (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Achievement of Crude Palm Oil (CPO) production at POM PT. Sinar Pandawa which exceeded the target was not in line with the absenteeism rate for the last three years, so it can be assumed that it was not from employee productivity. Therefore, employee work productivity still needs to be improved.  This study aims to determine the human resource development strategy carried out by POM PT.  Sinar Pandawa in increasing the work productivity of its employees.  The research method used is a qualitative approach with descriptive analysis, by collecting data through interviews, observation, and documentation.  The results showed the implementation of the human resource development strategy carried out by POM PT. Sinar Pandawa to increase employee productivity is to implement management functions, namely planning, organizing, supervising, and controlling all activities carried out by all departments in which there is a strategy for recruiting human resources, selecting, placing, and grouping employees, training, performance appraisal, as well as supervising and controlling company activities and employee attendance,  various forms of appreciation for employees, as well as creating a safe and comfortable ecosystem as well as providing appreciation and relevant facilities. POM PT. Sinar Pandawa uses training as a way to increase the productivity of its employees.